The following are the expressions,

sage: var('x1,t1,x2,t2,u,c',domain=RR);assume(u>0);assume(c>u);
(x1, t1, x2, t2, u, c)
sage: T1 = (t1-((u*x1)/(c^2)))/sqrt(1-((u^2)/(c^2)))
sage: T2 = (t2-((u*x2)/(c^2)))/sqrt(1-((u^2)/(c^2)))
sage: dT = T2-T1
sage: dt = t2-t1

Suppose I know that dT is in this form,

dT = a*dt + b,

Assuming I DID NOT know that,
a = 1/sqrt(1-((u^2)/(c^2)))   ,
b = (u*(x2 - x1))/((c^2)*sqrt(1-((u^2)/(c^2))))  ,

is there any way I can find 'a' and 'b' using Sage?

What if I didn't know that dT is in the form of a*dt + b, but just
knew dT in terms of x1,t1,x2,t2,u and c ?

Can I still express dT in terms of dt using sage?

-- 
To post to this group, send email to sage-support@googlegroups.com
To unsubscribe from this group, send email to 
sage-support+unsubscr...@googlegroups.com
For more options, visit this group at 
http://groups.google.com/group/sage-support
URL: http://www.sagemath.org

Reply via email to